Model Pembelajaran Two Stay Two Stray Tingkatkan Keterampilan Mengontruksi Teks Eksposisi - lis murtanti (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
This study aims to improve the quality of the learning process and learning outcomes in constructing the exposition text of class X TAV 2 in Vocational High School 3 Semarang students in the 2019/2020 school year using the Two Stay Two Stray learning model. This research is in the form of Classroom Action Research that uses 2 cycles with four processes, namely planning, action, observation, and reflection. Exposition text assessment in writing includes content, organization, vocabulary, language using, and mechanics. The results of the analysis shows that the increasing of the product in the pre-action stage was obtained by an average of 63.80 to 74.72 in cycle I. In stage II the average score was 81.67, the increasing is 17.87.